A high-efficiency thermal neutron detector based on thin 3D 10B4C converters for high-rate applications. (2nd October 2018) - Croci, Gabriele; Muraro, Andrea; Cippo, Enrico Perelli; Tardocchi, Marco; Grosso, Giovanni; Albani, Giorgia; Angella, Giuliano; Defendi, Ilario; Hall-Wilton, Richard; Höglund, Carina; Raspino, Davide; Rhodes, Nigel; et al.
Abstract: A new position-sensitive thermal neutron detector based on boron-coated converters has been developed as an alternative to today's standard 3 He-based technology for application to thermal neutron scattering. The key element of the development is a novel 3D 10 B4 C converter which has been ad hoc designed and realized with the aim of combining a high neutron conversion probability via the 10 B( n, α ) 7 Li reaction together with an efficient collection of the produced charged particles. The developed 3D converter is composed of thin aluminium grids made by a micro-waterjet technique and coated on both sides with a thin layer of 10 B4 C. When coupled to a GEM detector this converter allows reaching neutron detection efficiencies close to 50% at neutron wavelengths equal to 4 Å. In addition, the new detector features a spatial resolution of about 5 mm and can sustain counting rates well in excess of . The newly developed neutron detector will enable time-resolved measurements of different kind of samples in neutron scattering experiments at high flux spallation sources and can find a use in applications where large areas and custom geometries of thermal neutron detectors are foreseen.